Learning differences designing instruction with the 4MAT system (Utah : Linton, 1994)
This issue focuses on designing instruction to meet the learning style needs of all students
program 1 Understanding 4MAT - program 2 Utilizing 4MAT
Presenter: Bernice McCarthy
Keywords: Intructional systems -- Design